Volatility Spillovers Between BRIC © CC BY 4.0 and South African Stock Markets: Evidence from the COVID‑19 and Russia‑Ukraine Crises - Lorraine Muguto; Amy Moodley; Santhiran Pillay; Mcabangomuhle Zulu; Nonkululeko Vilakazi; Hilary Tinotenda Muguto; Paul Francois Muzindutsi (Review of Business and Economics Studies)
The aim of this study was to assess how global crises influenced volatility spillovers between BRIC and South African stock markets. In conducting the study, the methods employed are the generalized autoregressive conditional heteroskedasticity (GARCH) framework and the time-varying parameter vector autoregressive (TVP-VAR) Diebold-Yilmaz approach, based on a sample period segmented into pre-crisis, COVID-19, and Russia-Ukraine conflict phases. The study results revealed that volatility spillovers intensified during the COVID-19 pandemic due to economic disruptions and uncertainty. At the same time, the Russia-Ukraine conflict saw reduced spillovers due to geopolitical isolation and risk aversion. South Africa consistently emerged as a key volatility transmitter, particularly during crises. The study concludes that different global crises have distinct impacts on volatility transmission and should, therefore, be treated distinctly. The key contribution lies in enhancing the understanding of crisis-driven market integration, providing valuable insights for risk management and policy-making in interconnected financial systems.